Relationship Between Level Training Paramedics On Administration Hungarian Air Advanced And Rates Success In Ventilation Field In Cases To Stop Breathing In Al-Hilal Red Saudi (The Review of Diabetic Studies, 2025)
This study examines the relationship between the level of training that paramedics have taken in advanced airway management and the success of such paramedics to ventilate in real emergency scenarios especially during respiratory arrest cases attended to by the Saudi Red Cresser Authority. This research had both a descriptive and analytical research method which involved the use of a questionnaire given to 200 paramedics. The instrument gathered both demographic data and the statements that rated the training quality and field performance. The results showed that there was a obvious positive correlation between the high level of training and better efficiency in the process of ventilation in emergency situations and higher success. Another aspect in the study that has been identified as important is the need to have regular and updated training and close field supervision to not only improve the quality of pre-hospital care; but also the preparedness of paramedics to handle critical cases effectively. In the end, such outcomes will help in sustaining the professional competence and readiness in the Saudi Red Crescent Authority.